Cultural Diversity and the Performance of Multinational Firms - Gómez-mejia, Luis R.; Palich, Leslie E. (Journal of International Business Studies, 1997)
We test the hypothesis that culturally related international diversification will have a positive impact on firm performance and that the opposite will be true for culturally unrelated globalization. Cultural diversity for Fortune 500 firms was used to predict performance over a ten-year period (1985–1994), controlling for several organizational and industry characteristics. Regression tests using nine indicators of cultural diversity revealed no significant cultural effects. Alternate interpretations are offered.